A influência da envoltória no conforto térmico em salas de aula em climas tropicais - Perillo, Paulo José Lima (2018)
The well-being conditions provided by a quality school environment are fundamental to the improvement of student achievement. Promoting thermal comfort in classrooms without demanding high energy costs is a challenge in tropical regions, mainly because many buildings are adapted to receive the teaching functions. It is emphasized that wrapping plays an important role in the thermal comfort conditions in indoor environments and the retrofit of buildings needs to consider this. This work aims to analyze the influence of the thermal performance of the envelopes on thermal comfort in classrooms in two buildings of the Federal University of Goiás - Sant'Ana Unit and Areião Unit - located in the city of Goiás - GO. After analyzing the projects of the chosen buildings, two classrooms were selected in each building in the following orientations: northeast and northwest. The methods included: (a) the collection of climatic data - air temperature, relative humidity, wind speed and globe temperature - in the immediate environment and in the selected environments during the year 2017; (b) research of constructive information of the buildings under analysis; (c) application of a survey to the users of the selected rooms; (d) analysis of the immediate surroundings by the transect method and insolation analysis; (e) analysis of the thermal performance of the envelopes by the descriptive method of NBR 15.575 (ABNT, 2013); (f) quantification of thermal comfort by the PMV index (AMV / PPD) and Operative Temperature and Thermal Sensations of users. In this study, 448 answers were collected among university students in the Regional City of Goiás, UFG. The data allowed concluding that the immediate environment directly influences the thermal performance of the buildings, although there were no differences in temperature within the urban area. The thermal performance of the enclosures influences the degree of satisfaction of the users, and the building that did not meet the minimum requirements of the standard presented the highest percentage of thermal discomfort. It also has been observed that many users are acclimatized to the external environment, so they are not very satisfied with the acclimatized environments. These data are very important for professionals in the area who aim to adapt educational environments to the user's thermal comfort needs.